Los poemacidios - Sergio Delgado (Cuadernos LIRICO)
This article seeks to grasp the colour and taste of the "present" as they were to be experienced in the context of the year 1969. The present of a text, after all, is but a vanishing line, an unreachable horizon between an author and a reader, between what is written and what is to be read. This contribution focuses on several intimate, secret, almost invisible episodes in the lives of Amaro Villanueva and Juan L. Ortiz.